Methodology for the development of an ontology network on the Brazilian national system for the evaluation of higher education (ONTOSINAES) - Silva, Cleiton; Belo, Olando; Barros, Victor F A (Journal of Information Systems and Technology Management, 2018)
Ontologies occupy a central position in any conceptual model of the Semantic Web, aiming fundamentally to add explicit semantics to the contents available in the Web. In the domain of Brazilian higher education, especially with regard to the National System for the Evaluation of Higher Education (SINAES), still lacks a reference ontology that can provide a basic conceptualization common to the different stakeholders of the domain. In this work we discuss the role of an ontology network developed with the purpose of improving the quality of the data produced by the different actors, institutions and systems within the domain of SINAES, in addition to facilitating their publication as open and connected data. In particular, we highlight the importance of the NeOn methodology to be followed during the development of an ontology network, demonstrating its role in defining the life cycle and in the articulation of the various processes and activities in the OntoSINAES ontological network development process.